Thirteen-year follow-up of long-term treated psychotic disorder: personality aspects. (1st July 2022) - Fagerberg, Tomas; Söderman, Erik; Gustavsson, J. Petter; Agartz, Ingrid; Jönsson, Erik G.
Abstract: Objective: Personality is an aspect that can affect the symptoms and social function in individuals with psychotic disorders. Several studies have investigated personality in schizophrenia and other long-term psychotic disorders. No study has examined the stability of personality traits exceeding five years in patients with schizophrenia and related disorders. The aim of this study was to investigate the stability of personality traits over a 13-year period among patients with schizophrenia and related disorders and healthy individuals and to evaluate case-control differences. Methods: At three occasions during a 13-year period patients with schizophrenia and related disorders ( n  = 28) and healthy individuals ( n  = 57) completed Swedish universities Scales of Personality (SSP). Mean-level change and case-control differences were investigated for all the individuals using within- and between-subject analyses, respectively. Analyses were performed on three occasions for all 13 subscales and the three overall factors of SSP. Also, correlations, means, and SDs were calculated. Results: Tests of within-subject correlations showed differences in two subscales: Lack of Assertiveness, which were influenced by age, and Physical Trait Aggression, where patients' ratings were stable, whereas controls rated themselves less aggressive at a higher age. Between-subjects correlations showed differences regarding diagnosis, time, age, gender, or age × gender in nine of the 13 subscales as well as in factor Neuroticism. Conclusion: Long-term follow-up showed generally high stability of personality traits measured with SSP. Between-subject analyses over the 13 years showed that patients differed compared to controls for the SSP factor Neuroticism as well as the subscale Detachment, which is in accordance with previous studies within this population.